Turkey's mission impossible war and peace with the Kurds - Çandar, Cengiz, 1948- (Kurdish societies, politics, and international relations., 2020)
"Providing a unique record of the authoritarian, centralist and ultra-nationalist nature of the Turkish state manifested in Erdoğan's "New Turkey," Çandar challenges stereotyped and conventional views on Turkey and details account of the encounter between Turkey and the Kurds in historical perspective with special emphasis on failed peace processes"--